Effect of running classes on the stress level of combatants - Nataliia Krushynska; Iryna Kohut; Sergey Matveev; Marina Jagiello (Kharkiv State Academy of Physical Culture, 2022)
The full-scale war in Ukraine is having a significant psychological and physical impact on combatants. One of the negative consequences of war is combat stress, accompanied by the action of stress factors that negatively affect psychological and physical health, reducing the process of socialization to peaceful life. At the same time, there are not enough studies covering the solution of these issues with the help of adaptive physical culture (APC), which confirms the relevance of the chosen topic. Purpose: to determine the impact of running classes on combatants who have the consequences of combat stress. Material & Methods: the research was carried out on the basis of the National Council for Sports Rehabilitation of Defenders of Ukraine in Kyiv. It was attended by 40 combatants. The following methods were used in the course of the study: theoretical analysis and generalization of scientific and methodological literature, pedagogical testing, pedagogical experiment, methods of mathematical statistics. Results: at the end of the pedagogical experiment, the participants in the hostilities determined the level of stress according to the "Modified method for determining the level of stress by L. Ryder", before and after running classes. Based on the data after the study, it was found that at the initial stage, 77% of combatants had a high level of stress, and 13% had an average level of stress. At stage 2, after the use of APC (within 1 year), the level of stress among combatants was reduced to 50% - medium, 50% - low, which shows the effectiveness of the use of APC (running classes). Conclusions: a study was conducted with the determination of the level of stress according to the "Modified method of the level of stress according to L. Rieder" and the positive effect of running was shown. Measures are proposed to help reduce the level of stress among combatants. The dynamics of the results indicates the stability of reducing the level of combat stress with the help of running, which confirms the expediency of organizing the training process for combatants.